US tropical cyclone flood risk: Storm surge versus freshwater. Issue 12 (7th February 2022) - Tonn, Gina; Czajkowski, Jeffrey
Abstract: Despite persistent record‐breaking flood losses from tropical cyclones (TCs), the United States continues to be inadequately prepared for TC flood events, with the deficiency in residential flood insurance being a prime representation of this. One way to address this is through a better quantification of TC flood risk including variations associated with freshwater versus storm surge flood hazard and damage. We analyze actual residential flood claim data from the National Flood Insurance Program (NFIP) for the full set of all 28 significant US landfalling TC‐related flood events from 2001 to 2014 which we split by storm surge and freshwater. We illustrate key differences between the numbers of claims, paid claim amounts, and damage for freshwater and surge claims, as well as evaluate differences associated with flood zone, state, TC event, and flood depth. Despite the typical focus on surge TC flooding, freshwater flooding accounts for over 60% of TC paid claim and damage amounts. Surge flooding often occurs outside of high‐velocity flood zones, which is not reflected in the NFIP premiums. Statistical analysis indicates that depth‐damage ratios vary significantly by surge versus freshwater and by geography. State‐level analysis shows that land‐use policies and building codes likely affect differences in damage along with storm characteristics and geography. The findings highlight the need to mitigate and manage both freshwater and surge TC flood risk and for more individualized flood insurance premiums less tied to flood zone. It appears that the latter need may be addressed by the Federal Emergency Management Agency (FEMA)'s Risk Rating 2.0.